2019
DOI: 10.1029/2018jc014679
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eddies and Topography in the Export of Shelf Waters From the West Antarctic Peninsula Shelf

Abstract: Oceanic heat strongly influences the glaciers and ice shelves along West Antarctica. Prior studies show that the subsurface onshore heat flux from the Southern Ocean on the shelf occurs through deep, glacially carved channels. The mechanisms enabling the export of colder shelf waters to the open ocean, however, have not been determined. Here, we use ocean glider measurements collected near the mouth of Marguerite Trough (MT), west Antarctic Peninsula, to reveal shelf-modified cold waters on the slope over a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Our high-resolution model results suggest that about half of the volume transport of near surface coastal water due to trapping by cyclones may occur for small eddies that are missed by altimetry observations. This is consistent with Brearley et al (2019), who have shown that small scale eddies contribute to the export of cold shelf water to the open ocean off the Peninsula. Future satellite missions that will provide sea level anomalies in higher resolution (e.g., NASA's Surface Water and Ocean Topography mission-SWOT; Fu et al, 2012) will allow for investigating transport of coastal water rich in POC by small eddies based on observations.…”
Section: 1029/2020jc016791supporting
confidence: 92%
See 2 more Smart Citations
“…Our high-resolution model results suggest that about half of the volume transport of near surface coastal water due to trapping by cyclones may occur for small eddies that are missed by altimetry observations. This is consistent with Brearley et al (2019), who have shown that small scale eddies contribute to the export of cold shelf water to the open ocean off the Peninsula. Future satellite missions that will provide sea level anomalies in higher resolution (e.g., NASA's Surface Water and Ocean Topography mission-SWOT; Fu et al, 2012) will allow for investigating transport of coastal water rich in POC by small eddies based on observations.…”
Section: 1029/2020jc016791supporting
confidence: 92%
“…The configuration used for the WAP has 1.5 km horizontal resolution and 24 variable‐thickness vertical layers that are concentrated toward the top and bottom surfaces. The 1.5 km resolution model has been shown to simulate well small scale (∼5–10 km) eddy heat transport onto the WAP continental shelf (Graham et al., 2016) and larger scale eddy volume transport off the WAP continental shelf/slope (Brearley et al., 2019). It includes a dynamic sea ice model (Budgell, 2005) and simulates mechanical and thermodynamic interactions between the floating ice shelves in the model domain and the water cavity underneath (Dinniman et al., 2011; Holland & Jenkins, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep, steep canyons and other topographic features play a key role in the across-shelf exchange of properties along this and other Antarctic shelves (Moffat et al, 2009;Martinson and McKee, 2012). This exchange is strongly modulated by small ocean eddies that play a role on both the supply of heat and nutrients to the shelf (Moffat et al, 2009) as well as the export of shelf-modified waters to the open ocean (Brearley et al, 2019). Eddy-driven exchange is a key modulating factor of ocean properties around the continent, and this process is modulated by wind forcing (Thompson et al, 2014;Stewart and Thompson, 2015).…”
Section: Seawater Circulation and Exchangementioning
confidence: 99%
“…These authors did not discuss the circulation in Latady Trough, and this region's contribution to heat transport toward the BellS ice shelves remains unconstrained. The generation of cyclonic circulations supported by glacially carved troughs is a feature that is common throughout the WAP (Brearley et al, 2019;Savidge & Amft, 2009). Coupled ice-ocean simulations carried out by Assmann et al (2005) found the region to be dominated by a large-scale cyclonic circulation, although the model did not resolve circulation features in individual troughs.…”
mentioning
confidence: 99%